2016
DOI: 10.1038/nn.4282
|View full text |Cite
|
Sign up to set email alerts
|

Ryk controls remapping of motor cortex during functional recovery after spinal cord injury

Abstract: Limited functional recovery can be achieved with rehabilitation after incomplete spinal cord injury. Eliminating the function of a repulsive Wnt receptor, Ryk, by either conditional knockout in the motor cortex or monoclonal antibody infusion, resulted in increased corticospinal axon collateral branches with pre-synaptic puncta in the spinal cord and enhanced recovery of forelimb reaching and grasping function following a cervical dorsal column lesion. Using optical stimulation, we observed that motor cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 35 publications
5
67
0
Order By: Relevance
“…Using optogenetic approaches, it was found that cortical areas dedicated to eliciting motor behaviors in the limbs were re‐mapped after forelimb training and C5 spinal cord injury. Ryk‐deleted mice had a larger cortical area involved in flexor (triceps) function and an overall increase in area dedicated to limb movement compared with control mice (Hollis et al, ). This work shows that an understanding of how axon guidance molecules exert their functions during development can lead to the conception of new strategies for enhancing repair and plasticity in the injured adult nervous system.…”
Section: Guidance Cuesmentioning
confidence: 99%
“…Using optogenetic approaches, it was found that cortical areas dedicated to eliciting motor behaviors in the limbs were re‐mapped after forelimb training and C5 spinal cord injury. Ryk‐deleted mice had a larger cortical area involved in flexor (triceps) function and an overall increase in area dedicated to limb movement compared with control mice (Hollis et al, ). This work shows that an understanding of how axon guidance molecules exert their functions during development can lead to the conception of new strategies for enhancing repair and plasticity in the injured adult nervous system.…”
Section: Guidance Cuesmentioning
confidence: 99%
“…Ryk plays critical functions in Wnt‐mediated axon guidance, as first demonstrated for the Derailed receptor, the Drosophila homolog of Ryk (Yoshikawa et al, ). Studies in vertebrate systems have cemented Ryk's critical role as a regulator of neurite outgrowth, acting largely as repulsive cue that inhibits axon growth (Liu et al, ; Schmitt et al, ; Liu et al, ; Hollis et al, ) and dendritic arborization (Lanoue et al, ). In addition, Ryk has also been implicated in mediating neurite outgrowth (Lu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results reinforce previous studies (Wang et al 2018) documenting the power of retro-AAV, tissue clearing, and light sheet imaging for obtaining quantitative and complete identification of the components of the CST. Also, our data on the normal projection patterns of CST axons from different parts of the cortex to different levels and laminae of the spinal cord provide novel insights into topographic specificity of normal CST projections, which will aid in identifying differences in projection patterns in mice carrying mutations, in detecting changes in patterns of projection due to regenerative growth following injury (Hollis et al 2016) and form part of the basis for comparisons of CST projection patterns between strains and species.…”
Section: Discussionmentioning
confidence: 98%